A novel approach to characterize dynamic pressure on lower limb wearing compression cycling shorts. Issue 8 (2nd August 2016) - Luo, Shunhua; Wang, Jianping; Shi, Hui; Yao, Xiaofeng
Abstract : Dynamic pressure plays an important role in the cyclists' performance and comfort. The purpose of this study is to qualitatively characterize dynamic pressure on lower limb with compression cycling shorts in a continuous cycling motion. Ten male cyclists participated in this study while wearing six pairs of compression cycling shorts with different ease allowances. Eight pressure measurement points were selected based on skeletal muscle simulation and surface curvature. A novel approach was developed to transform consecutive static pressures into dynamic pressure with interpolation technique. Firstly, a circular motion was evenly divided up into 12 postures. Secondly, static pressures in 12 postures were consecutively measured with an air pack-type pressure measuring instrument. Lastly， dynamic pressure was achieved with cubic spline interpolation in MATLAB based on static pressures in 12 postures. It was found that dynamic pressures at eight points were great difference. Maximum dynamic pressure at eight points was produced when pedal was at the top. Pressure linearly rose when ease allowance was gradually reduced at seven points (except at abdomen). Dynamic pressure fluctuation at four points (middle rectus femoris, middle biceps femoris, distal vastus medialis, and distal vastus lateralis) was significantly related with muscle activation ( p  < 0.01). Dynamic pressure at convex point of hip was mainly depended on skin deformation and surface curvature. Dynamic pressure of convex point of abdomen was controlled by breath rhythm. The findings are helpful to propose reasonable ease allowance at different parts of compression cycling shorts and provide theoretical guideline for fashion designers to improve pressure comfort and motion performance.